The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1109/tpwrs.2017.2786470
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Benefits of Dynamic Line Rating Under Multiple Sources of Uncertainty

Abstract: Abstract--This paper analyses the benefits of dynamic line rating (DLR) in the system with high penetration of wind generation. A probabilistic forecasting model for the line ratings is incorporated into a two-stage stochastic optimization model. The scheduling model, for the first time, considers the uncertainty associated with wind generation, line ratings and line outages to co-optimize the energy production and reserve holding levels in the scheduling stage as well as the re-dispatch actions in the real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…For a risk-neutral approach, the ratio between reserve costs (0.085%) and benefits (1.01%), i.e. a ratio of 1 to 12, is close to that found in [22].…”
Section: A Traditional Strategiessupporting
confidence: 69%
See 2 more Smart Citations
“…For a risk-neutral approach, the ratio between reserve costs (0.085%) and benefits (1.01%), i.e. a ratio of 1 to 12, is close to that found in [22].…”
Section: A Traditional Strategiessupporting
confidence: 69%
“…The problem to be solved is the optimal operation of a grid on which some lines are equipped with DLR. It is similar to that formulated in [18] and [22], which assess the DLR value in grid management. Since several uncertainties are involved, a stochastic optimisation approach is applied.…”
Section: Modelling Approachmentioning
confidence: 75%
See 1 more Smart Citation
“…The results showed that the coordination between battery energy system and wind farms can significantly reduce the operation cost and renewable energy curtailment. F. Teng et al analyzed the benefits of dynamic line rating in the transmission system [13]. A scheduling model with consideration of multiple sources of uncertainty including wind generation, line ratings, and line outrages was proposed.…”
Section: Power System Flexibilitymentioning
confidence: 99%
“…DTR bring us several benefits [4]. It allows the use of existing transmission assets efficiently, thus improving economic benefits, allows deferral of new transmission lines, it makes it possible to manage more easily contingency conditions.…”
Section: Introductionmentioning
confidence: 99%